Factors affecting the utilisation of postpartum care among young mothers in Bangladesh - Mosiur Rahman, Md.; Haque, Syed Emdadul Mdadul; Zahan, Sarwar (© 2011 Blackwell Publishing Ltd., 2016)
This article was published in the Health and Social Care in the Community [© 2010 Blackwell Publishing Ltd.] and the definite version is available at : http://doi.org/10.1111/j.1365-2524.2010.00953.x. The Journal's website is at: http://onlinelibrary.wiley.com/doi/10.1111/j.1365-2524.2010.00953.x/abstract;jsessionid=B37DAD816A8607C815ADF16E5CFA7685.f03t02